If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -6 = -24 + 2x Reorder the terms: -6 + 6x = -24 + 2x Solving -6 + 6x = -24 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -6 + 6x + -2x = -24 + 2x + -2x Combine like terms: 6x + -2x = 4x -6 + 4x = -24 + 2x + -2x Combine like terms: 2x + -2x = 0 -6 + 4x = -24 + 0 -6 + 4x = -24 Add '6' to each side of the equation. -6 + 6 + 4x = -24 + 6 Combine like terms: -6 + 6 = 0 0 + 4x = -24 + 6 4x = -24 + 6 Combine like terms: -24 + 6 = -18 4x = -18 Divide each side by '4'. x = -4.5 Simplifying x = -4.5
| X+9+(-11)=2 | | (5-2i)/(1-3i) | | 56=5w+16 | | -2+3y=-23 | | 26=x/4-17 | | cot(10x)=cot(5x) | | 5x(4.1+b)=45 | | tan(10x)=tan(5x) | | 67.2=3.5*q | | 150-20x+6x=6+11 | | -2m=-9 | | 4x^3+40x^2+96x+36=0 | | -x+44=235 | | (X^2)8= | | 3=-3(y-5)-2(y=1/3) | | 125=-v+214 | | 19-10x=34 | | 5-1/7x=-6 | | 0.6*x=31.2 | | 0.875+t=0.25 | | 15x+22=28 | | 36w=-8 | | -2x(x-3)+5x=-15 | | 5n^2=5-24n | | -7y+5y+15=-5 | | 8(5r-9)=33-4r | | 0x+5=3 | | 8w-32+3w=34 | | X/9-17=-4 | | 4p-4=2+7p | | -8(c-10)=(c-3) | | 10x+20=16x-16 |